Job Safety Analysis of Confined Space on Fertilizer Division on Seasoning Industries - Emon Rifa'i; Rifky Maulana Yusron; Booi Kam (Fakultas Teknik Universitas Muria Kudus, 2025)
Confined space activities in fertilizer production present significant risks, including toxic gas exposure, oxygen deficiency, fire and explosion hazards, and physical or ergonomic challenges. This study applies the Job Safety Analysis method to systematically identify hazards, assess risks, and establish effective control measures during the repair and maintenance of the FRP Pond 22000 Kl at the fertilizer division on seasoning industry. The methodology consisted of six structured stages: job selection, task breakdown, hazard identification, risk control, verification, and monitoring. Hazard identification was carried out through field observation, consultation with Health, Safety, and Environment officers, and adherence to national regulatory standards. Results revealed that atmospheric testing prior to entry was essential, with oxygen levels recorded at 20.8% and toxic gases, within safe limits. The JSA identified potential risks at each task stage and applied control measures following the hierarchy of controls, including engineering controls ventilation, and gas detection. While administrative measures section permit towork system, time restrictions, and health certificates. On energy isolation is installation Lock Out Tag Out. The essential is mandatory of personal protection equipment. Collaborative inspections by contractors, supervisors, and Health, Safety, and Environment staff reinforced compliance and improved communication. The study concludes that job safety analysis is not only a compliance requirement but also a practical framework for hazard anticipation, safety culture reinforcement, and operational continuity. It is recommended that future practice integrates digital job safety analysis systems, real-time monitoring, and enhanced training to strengthen confined space safety in fertilizer production and other high-risk industries.